Effect of multi-walled carbon nanotube on thermophysical properties of polyester and mineral oil. (2022) - Joshi, Yogesh G.; Zanwar, Dinesh R.; Tiwari, Rohit; Wastrane, Aniket; Gorle, Shubham; Barai, Sanket
Abstract: In the past few decades, multi-walled carbon nanotubes (MWCNT) have been used to increase the efficiency of thermal systems. Many nanofluids were synthesized using MWCNT, using which the thermophysical properties of normal fluid have enhanced. Out of these fluids, polyester oil (POE) and mineral oil (MO) are the oils that are used in the refrigeration sector. In this paper, MWCNT has been used to increase the thermophysical properties of these two oils. Two different types of nanoparticle concentrations of 0.05 wt% and 0.1 wt% MWCNT have been used. The thermal conductivity and viscosity of both these types of concentrations have been measured theoretically and experimentally. In theoretical evaluation, the Hamilton model is used for the evaluation of thermal conductivity and the Brinkman model to evaluate the viscosity. The investigation concluded that the thermophysical properties of POE and mineral oil increases through MWCNT nanoparticles dispersion. The result obtained from the theoretical model and experimentation was observed to followed a similar pattern. Out of the two oils, the highest thermal conductivity was gained by using 0.1 wt% MWCNT with POE oil. The thermal conductivity of POE oil increased by 1.09 W/mk and that of mineral oil increased by 0.91 W/mk. Also, the viscosity of POE increased by 26.4 % and that of mineral Oil by 24.4 % by using 0.1 wt% of MWCNT. The optimal concentration of MWCNT is utilized to avoid agglomeration. It is observed that up to 0.1 wt% of MWCNT nanoparticle concentration, no sedimentation or agglomeration was observed in POE and MO based nanosuspensions.